1956
DOI: 10.1136/hrt.18.1.49
|View full text |Cite
|
Sign up to set email alerts
|

THE INFLUENCE OF AGE ON THE HAeMOGLOBIN LEVEL IN CONGENITAL HEART DISEASE

Abstract: The haemoglobin content of the blood is a convenient out-patient test, and it has some value in the assessment of cyanotic heart cases both before and after operation (Campbell and Deuchar, 1953 and Campbell, Deuchar, andBrock, 1954). However, the theoretical background to variations of the hemoglobin level in congenital heart disease is not well understood.When the oxygen tension of arterial blood is reduced by altitude, it is comparatively easy to demonstrate an inverse relationship between oxygen tension a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1957
1957
1966
1966

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Brinton (1951) also showed that hiemoglobin concentration was not related directly to the arterial oxygen saturation and that the packed cell volume and absolute red cell counts were more valuable. Shephard (1956), too, confirmed that the hiemoglobin increased with age in patients with cyanotic heart disease, though his subjects were over 3 years of age. In another group of patients (unpublished observations) we have observed that infants with cyanotic heart disease show evidence of iron deficiency.…”
Section: Discussionmentioning
confidence: 67%
“…Brinton (1951) also showed that hiemoglobin concentration was not related directly to the arterial oxygen saturation and that the packed cell volume and absolute red cell counts were more valuable. Shephard (1956), too, confirmed that the hiemoglobin increased with age in patients with cyanotic heart disease, though his subjects were over 3 years of age. In another group of patients (unpublished observations) we have observed that infants with cyanotic heart disease show evidence of iron deficiency.…”
Section: Discussionmentioning
confidence: 67%